Generation Z: Person Organization-Fit, Life Balance and Psychological Empowerment for Work Totality - Kurniawan, Alvin; Rahman Shaleh, Abdul (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Human functioning in a professional environment is becoming more efficient; however, this is not always commensurate with increased objectivity. Today, members of Generation Z express concerns about various work disruptions, including negative impacts on mental health caused by unhealthy work environments, which are often characterized by disrupted deadlines. This condition often leads to delays and ultimately has an impact on overall performance. The purpose of this study was to determine the effect of person-organization-fit, work-life balance and psychological empowerment on the totality of work. This study uses a quantitative approach with multiple regression and adaptation of measuring instruments derived from previous studies, with the research subjects being Generation Z who work in the South Jakarta area. The sampling technique used was non-probability sampling, with a total of 208 respondents. The results of the study indicate that the totality of work is influenced by person-organization fit, work-life balance and psychological empowerment, with the greatest influence on work-life balance on the totality of work and the smallest influence on psychological empowerment on the totality of work of Generation Z, together person-organization fit, work-life balance and psychological empowerment affect the totality of work of Generation Z. Fungsi manusia dalam lingkungan profesional menjadi semakin efisien; namun, hal ini tidak selalu sebanding dengan peningkatan objektivitas. Saat ini, anggota Generasi Z mengungkapkan kekhawatiran terkait berbagai gangguan pekerjaan, termasuk dampak negatif terhadap kesehatan mental yang disebabkan oleh lingkungan kerja yang tidak sehat, yang sering kali ditandai dengan tenggat waktu yang terganggu. Kondisi ini sering kali berujung pada penundaan dan akhirnya berdampak pada penurunan kinerja secara keseluruhan. Tujuan penelitian ini untuk mengetahui pengaruh person organization-fit, keseimbangan hidup dan pemberdayaan psikologis terhadap totalitas kerja. Penelitian ini menggunakan pendekatan kuantitatif dengan regresi berganda dan adaptasi alat ukur berasal dari penelitian sebelumnya, dengan subjek penelitian adalah generasi Z yang bekerja di kawasan Jakarta Selatan. Teknik sampling yang digunakan adalah non-probability sampling, dengan jumlah responden sebanyak 208 orang. Hasil penelitian menunjukkan bahwa totalitas kerja di pengaruh oleh person-organization fit, keseimbangan kerja & hidup serta pemberdayaan psikologis, dengan pengaruh terbesar pada keseimbangan kerja & hidup terhadap totalitas kerja dan pengaruh terkecil pada pemberdayaan psikologi terhadap totalitas kerja generasi Z, secara bersama-sama person-organization fit, keseimbangan kerja & hidup pemberdayaan psikologis secara bersama-sama mempengaruhi totalitas kerja generasi Z.